# 5/2t - t = 3 + 3/2t please solve

### 3 Answers | Add Yours

5/2t - t = 3 + 3/2t

We will combine like terms,

==> 5/2t - 3/2t - t= 3

==> (5-3)/2t - t = 3

==> 2/2t - t = 3

==> 1/t - t= 3

==> Multiply by t.

==> 1 - t^2 = 3t

==> t^2 + 3t -1 = 0

==> t= [ -3 + sqrt(9+4)/ 2 = (-3+sqrt13)/ 2

==> t2= (-3-sqrt13)/2

Then we have two solution.

**==> t= { (-3+sqrt13)/2 , (-3-sqrt13)/2 }**

5/2t - t = 3 + 3/2t

First combine the like terms ( 5/2t and -t )

By combining the like terms, you should get

**3/2t = 3 + 3/2t **subtract 3/2t on both sides

By subtracting you should get

**0 = 3 **

**since 0 does not = to 3 your answer is no solution**

5/2t-t= 3+3/2t

One t is basically the same as 2/2t so

5/2t-2/2t= 3+3/2t

Simplify on the left first

3/2t=3+3/2t

Subtract 3/2t from both sides but...

Since 3/2t-3/2t= 0, this means that there is no solution to this problem. Since the variables cancel each other out.